POLITIK KEBIJAKAN PARIWISATA DALAM PENGEMBANGAN WISATA PANTAI TANJUNG LAPIN DI KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS TAHUN 2023 - ', Nurvitasari; Susanto, Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Tourism policy is a manifestation of the integration of public policy and tourism sector development strategies oriented towards community welfare and environmental sustainability. In the context of Bengkalis Regency, the tourism sector is a selected government affair with strategic potential to increase Regional Original Income (PAD) and strengthen the region's image. The purpose of this study is to examine the tourism policy applied to the development of Lapin Beach and the factors influencing it. Tourism, as a strategic sector, requires appropriate government policies to improve community welfare while strengthening the attractiveness of tourist destinations.The research method used was descriptive qualitative, with data collection techniques through observation, in-depth interviews, and documentation. Informants came from the Bengkalis Regency Tourism Office, the Regional People's Representative Council (DPRD), NGOs, and local communities. The collected data was then analyzed through data reduction, data presentation, and conclusion drawing to illustrate the political realities of tourism policy in the field.The research results show that Lapin Beach development policies still face several obstacles, including budget constraints, lack of community participation, weak promotion, and suboptimal tourism infrastructure. Although the government acts as a facilitator, the dominance of local elites and minimal community involvement have led to unequal benefits. Therefore, policy transparency, increased community participation, and protection of socio-ecological aspects are essential to realizing inclusive and sustainable tourism development in North Rupat District, Bengkalis Regency. Keywords : Policy Politics, Tourism, Tourism Object Development, Lapin Beach